2010
DOI: 10.1210/en.2010-0702
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Responses to Fasting Indicate Metabolic Reprogramming Away from Glycolysis Toward Lipid Oxidation

Abstract: Nutrient-sensitive hypothalamic neurons regulate energy balance and glucose homeostasis, but the molecular mechanisms mediating hypothalamic responses to nutritional state remain incompletely characterized. To address these mechanisms, the present studies used quantitative PCR to characterize the expression of a panel of genes the hypothalamic expression by nutritional status of which had been suggested by DNA microarray studies. Although these genes regulate a variety of function, the most prominent set regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 50 publications
6
53
1
Order By: Relevance
“…Furthermore, fasting induces the mobilization and metabolism of lipids in the hypothalamus that are required for molecular responses to fasting [46]. Consistent with these observations, Cpt1a in the VMH is induced by fasting in the VMH but not the cortex, rapidly reversed 4 hours after feeding [47]. FFAs are normally elevated by fasting, leading to the activation of the nuclear receptor peroxisome proliferator-activated receptor (Ppar)-alpha, which then induces Cpt1a (stimulating metabolism of FFAs) as well as genes that inhibit glucose metabolism, such as pyruvate dehydrogenase kinase, isozyme 4Pdk4 (PDK4) [48].…”
Section: Vmh Neurons Determine Glucose Homeostasis Energy Balance Amentioning
confidence: 82%
“…Furthermore, fasting induces the mobilization and metabolism of lipids in the hypothalamus that are required for molecular responses to fasting [46]. Consistent with these observations, Cpt1a in the VMH is induced by fasting in the VMH but not the cortex, rapidly reversed 4 hours after feeding [47]. FFAs are normally elevated by fasting, leading to the activation of the nuclear receptor peroxisome proliferator-activated receptor (Ppar)-alpha, which then induces Cpt1a (stimulating metabolism of FFAs) as well as genes that inhibit glucose metabolism, such as pyruvate dehydrogenase kinase, isozyme 4Pdk4 (PDK4) [48].…”
Section: Vmh Neurons Determine Glucose Homeostasis Energy Balance Amentioning
confidence: 82%
“…Our initial screen assessed gene expression in a hypothalamic dissection that includes the VMN and the ARC, a portion of the PVN, but relatively little lateral hypothalamus (18). Extending these studies to microdissected nuclei, we observed that fasting induced Fkbp51 in all of these hypothalamic nuclei in both mice and rats (although not significantly in mouse PVN).…”
Section: Discussionmentioning
confidence: 96%
“…This was associated with a shift away from hypothalamic glucose metabolism and toward metabolism of alternative substrates, as we had previously observed during fasting, and which would be expected to cause obese phenotypes [52], as well as a reduction of hypothalamic POMC, which we had previously demonstrated is causally associated with obese and diabetic phenotypes [51][52][53]. We went on to demonstrate that experimental manipulation toward hypothalamic lipid metabolism (by over-expressing Cpt1a) also promoted obese phenotypes, including reduction of hypothalamic POMC, although not as robustly as inhibiting Cbp [51].…”
Section: Discussionmentioning
confidence: 62%